Morphology and molecular systematic of marine gregarines (Apicomplexa) from Southwestern Atlantic spionid polychaetes - Rueckert, S. (2018)
Gregarines are a common group of parasites that infect the intestines of marine invertebrates, and particularly polychaetes. Here, we describe for the first time four gregarine species that inhabit the intestines of three spionid species: Dipolydora cf. flava, Spio quadrisetosa and Boccardia proboscidea from the Patagonian coast, Argentina, using light and scanning electron microscopy and molecular phylogenetic analyses of small subunit (SSU) rDNA sequences. Even though the spionid species thrive in the same environments, our results showed a high host specificity of the gregarine species. Selenidium cf. axiferens and Polyrhabdina aff. polydorae were both identified from the intestine of D. cf. flava. The new species, Polyrhabdina madrynense sp. n. and Selenidium patagonica sp. n., were described from the intestines of S. quadrisetosa and the invasive species B. proboscidea, respectively. All specimens of D. cf. flava and S. quadrisetosa were infected by gregarines (P = 100%), recording the highest mean intensity values of infection (MI = 80; 60 respectively), in contrast to B. proboscidea (P = 60%; MI = 38). We associated this finding with the recent invasion of this host. It is expected that in the future, an increase of its population density might favour a rising intensity of this gregarine infection.